The Priest, the Sex Worker, and the CEO: Measuring Motivation by Job Type - Arnulf, Jan Ketil; Nimon, Kim; Larsen, Kai Rune; Hovland, Christiane V.; Arnesen, Merethe (Frontiers in Psychology, 2020)
This study uses latent semantic analysis (LSA) to explore how prevalent measures (items) of motivation are interpreted across very diverse job types. Building on the Semantic Theory of Survey Response (STSR), we establish a measure called “semantic compliance”, which is the degree to which an individual’s responses follow a semantically predictable pattern. This allows us to examine how context, in the form of job characteristics, influences respondent interpretations of items. In total, 399 respondents from 18 widely different job types (from CEOs through lawyers, farmers and artists to sex workers and professional soldiers) self-rated their work motivation on eight commonly applied motivational scales from the research literature. A second sample served as an external evaluation panel (n = 30) and rated the 18 job types on their perceived job characteristics. We then applied LSA to check if the groups differed in their interpretations of items. The findings indicate that while job characteristics do predict the motivational score levels significantly, job characteristics also predict semantic compliance usually at a lesser but significant magnitude. Combined, semantic compliance and attitude strength explained up to 41% of the differences in variance between the job types. The variation in semantic compliance was also significantly related to job characteristics as rated by an external panel. Our findings indicate that people in different contexts interpret items differently to a degree that substantially affects their score levels. We discuss how future measurements of motivation may improve by taking semantic compliance and the STSR perspective into consideration.